Assessments of Collection Security Management in Academic Libraries:A Case Study of Central University Library - Yamson, George Clifford; Cobblah, MacAnthony (European Scientific Journal, ESJ, 2017)
Librarians and libraries across the world are faced with the issues of security of their collection. The issue of collection security in libraries in the developing countries is worsened by low funding for libraries. In Ghana, the issue of collection security management often poses a tremendous problem to many libraries particularly academic libraries due to the lack of properly documented collection security policy. There is a compelling need for librarians to put in place measures that would effectively monitor crime, mutilation and abuses on library staff and collection, or else academic libraries will soon be empty. This study was conducted to determine the operationalization of collection security management procedures at the library of Central University The university was conveniently selected for the study, with studentsâ€™ population totalling 8000 and library staff of 33 both professional and paraprofessional. A statistical table was used to determine the sample frame and size for the studentsâ€™ population resulting with a sample size of 370 for students with a confidence level of 95%. A structured questionnaire was administered to the participants. Twenty (20.8%) of the users surveyed admitted that stealing and mutilation were common phenomena among library users. Limited copies of library books, cumbersome borrowing procedure, and high cost of photocopying and frequent breakdown of copiers were some of the causes of library materials theft and mutilation. The study revealed that Central University library suffered adversely from security issues and other anti-social menace and that the introduction of security policy, library surveillance and devices (CCTV) would drastically improve the situation. The study recommended further that theft mutilation of books and other security breaches can be checked by staff being vigilant and also carrying out â€œsecurity patrolsâ€.